Computational framework for a railway bridge maintenance strategies affected by gradual deterioration - António Abel Henriques (2018)
Bridges present valuable assets for the rail network by providing cross critical links such as waterways, valleys, and other types of facilities. However, these types of structures, during their life-cycle, are exposed to several threats such as natural hazards and deterioration. In fact, the lack of maintenance can lead to large consequences either for the structure, such as the partial or total collapse of the system, or for people. To assess the condition state of bridges, several performance indicators, of both quantitative and qualitative nature, have been proposed over these last decades by several researchers. Such indicators present a valuable information about the actual condition of the bridge to avoid undesirable consequences. These performance indicators are assessed over time through predictive models and can be determinist or probabilistic. The latter has been largely applied once they allow considering uncertainties associated with deterioration of the bridge. It is known that the deterioration of an infrastructure it is due to progressive deterioration (e.g., corrosion of the reinforcement, cracking of the concrete) and shock deterioration (e.g. earthquakes, collisions, floods). The idea of this paper is then to analyse a railway bridge and develop a framework that can consider gradual degradation to develop an optimal maintenance schedule.